Higher Test Scores or More Schooling? Another Look at the Causes of Economic Growth (2013)
I use a dynamic augmented Solow model to estimate the effects of students’ test scores and investment in schooling on economic growth rates in 49 countries during 1985-2005. In the complete data set, either average test scores or investment in schooling explain economic growth rates, and more of either causes growth. Further analysis reveals that higher test scores only raised growth rates in countries with low average levels of schooling. In countries with more than 7.5 years of schooling attainment in 1985, more investment in schooling raised growth rates, but higher average test scores did not.